Strategic Redistricting - Gul, Faruk; Pesendorfer, Wolfgang (American Economic Review, 2010)
Two parties choose redistricting plans to maximize their probability of winning a majority in the House of Representatives. In the unique equilibrium, parties maximally segregate their opponents' supporters but pool their own supporters into uniform districts. Ceteris paribus, the stronger party segregates more than the weaker one, and the election outcome is biased in the stronger party's favor and against the party whose supporters are easier to identify. We incorporate policy choice into our redistricting game and find that when one party controls redistricting, the equilibrium policy is biased towards the preferences of the redistricting party's supporters. (JEL C72, D72)